DIVERSITY OF PLANTS NATURALLY GROW IN TROPICAL DRY FOREST (T-df) OF BUKIT JIMBARAN BALI - Sujarwo, Wawan; Arinasa, Ida Bagus Ketut (Teknologi Indonesia, 2013)
Bukit Jimbaran Bali is considered one of the dry areas on Bali Island. The climate is very dry during the year and has very limited rainfall in the rainy season. The aim of our study is to review the ecology of natural regeneration of T-df, focusing on how the available information can be used to facilitate the recovery of these forests in disturbed areas. Tropical dry forest around Udayana University, which is situated in Bukit Jimbaran Bali, was selected as the investigation area since there was an ongoing CSR (corporate social responsibility) project for establishing urban forest at Udayana University. Sampling plots were established to determine plant diversity of seedlings, saplings, poles, and trees. Research results revealed high diversity of seedlings (40 species) and saplings (35 species) while trees were limited (11 species). We have come to the conclusion that groundcover diversity is high enough (75 species) even though the soil depth is very thin. In addition, there was abundant Acacia auriculiformis which is considered as an invasive species in the area.